CARING THROUGHOUT LIFE: PECULIARITIES OF LONG-TERM CARE FOR PUBLIC POLICIES WITHOUT AGEISM - Karla Cristina Giacomin; Paulo José Fortes Villas Boas; Marisa Accioly Rodrigues da Costa Domingues; Patrick Alexander Wachholz (Brazilian Society of Geriatrics and Gerontology, 2021)
None.